Analisis Risiko Produksi Kentang di Desa Sarimukti Kecamatan Pasirwangi Kabupaten Garut - Suhandi, Raisya Alviani Puteri; Kusumo, Rani Andriani Budi; Hapsari, Hepi; Heryanto, Mahra Arari (Universitas Galuh, 2025)
Potatoes are a horticultural commodity with high economic value. Potato production involves uncertainty and risks due to unpredictable seasons and high production costs, especially for seeds. The objective of this study is to identify risk events, sources of risk, and formulate the most effective risk control strategies for potato production in Sarimukti Village, Pasirwangi District, Garut Regency. The research location was purposively chosen with the consideration that Pasirwangi District is a potato production center in West Java. This study uses a qualitative method with a case study approach. The informants in this study consisted of 6 people. The data analysis technique used in this study is the House of Risk (HOR). The results of the study indicate that there are 28 risk events in potato vegetable production. The event with the highest impact is plant death. 18 of risk and 8 risk sources were identified. The sources of risk with the highest occurrence rate are non-certified seeds and unpredictable seasons. Industrial potato production was identified with 24 risk events, with the highest impact being plant death. 17 of risk were identified with 7 sources. The most frequently occurring risk source is the unpredictable season. There are 11 proposed risk control action strategies that can be applied to reduce risk. The most effective risk control action strategy for potato vegetable production is to purchase potato seeds directly from Balitsa or trusted seed breeders, while the most effective action strategy for industrial potato production is to determine the planting schedule for potatoes and crop rotation.